The Practice of Nonviolence: Teaching an Undergraduate Course in Nonviolent Communication - Sharon Lauricella (Central States Communication Association, 2019)
This Best Practices article outlines 10 tips relative to teaching a course in Nonviolent Communication (NVC). It outlines suggestions for readings, activities, and projects throughout a semester-long undergraduate course. The article addresses how students can learn both the theory and practice of nonviolence by means of readings and activities that address social problems such as sexism, racism, bias, and violence against oneself and the earth. Specific suggestions are provided for creative ways in which students can be engaged with readings so that they have ownership of their in-class experience. Details regarding an independent long-term project providing freedom of creativity in out-of-class work are included, as well as suggestions for interactive, face-to-face activities in class.